Interactions entre le loup gris, le caribou forestier et l'orignal en forêt boréale aménagée - Courbin, Nicolas (Université Laval, 2013)
My thesis explores the changes in behavioral strategies by the gray wolf (Canis lupus), moose (Alces alces) and forest-dwelling caribou (Rangifer tarandus caribou), in response to boreal forest management. I studied the factors that determine the spatial distribution of the three species, first by analyzing their movements and habitat selection, and then by assessing the predator-prey spatial game. My first chapter reveals that differences in movement tactics between the predator and its prey create asymetric relative probability of encounter between wolves and either of their prey along their movement paths. For example, given the time spent in the different land cover types along their paths, caribou had a relatively high risk of encountering wolves in regenerating cuts, while wolves had a relatively low probability of encountering caribou in these cuts. Overall, wolves intersected the paths of moose more often than those of caribou. My second chapter demonstrates that logging influences the residency time and inter-patch movement probabilities of caribou and moose by decreasing habitat connectivity. Graph theory showed that both prey species avoided network nodes (i.e., species-specific high-quality patches) surrounded by cuts and roads. Prey reduced their residency time in these nodes when they had to make relatively long inter-node movements to get there. Wolves selected the most connected nodes within their prey’s network, a selection that was even stronger than the selection for areas of high utilization distribution of its prey. My third chapter shows that from December to May, the relative probability of co-occurrence between wolf and caribou was highest in the vicinity of cutblocks areas, in the forest blocks protected from harvesting for the conservation of caribou. The consideration of predator-prey spatial relationships is therefore essential to the development of efficient management plans aimed at species recovery. My thesis underscores the major impact of human activities on habitat selection ...